Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - Chapters 1-7 Cumulative Review Problem Set - Page 324: 48



Work Step by Step

First, we factor the expression by using the trinomial rules of factoring. Then, we equate the resultant factors to zero. $x^{2}+5x-6=0$ $x^{2}+6x-1x-6=0$ $x(x+6)-1(x+6)=0$ $(x+6)(x-1)=0$ $(x+6)=0$ and $(x-1)=0$ $x=-6$ and $x=1$ Therefore, the solution set is {$-6,1$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.